Is Intensive Measurement of Body Image Reactive? A Two-Study Evaluation Using Ecological Momentary Assessment Suggests Not - Heron, Kristin E. (2012)
Intensive assessment methods (e.g., Ecological Momentary Assessment [EMA]) are increasingly used to capture body image experiences in daily life. One concern with EMA is multiple assessments may increase reactivity to internal or external cues, potentially biasing measurement. Reactivity to EMA was evaluated in two studies (Study 1: N = 63 female undergraduates, Study 2: N = 131 women with high body dissatisfaction/disordered eating). Participants completed five daily surveys on handheld computers for 1–2 weeks and body image-related questionnaires at the start and end of each study. Results showed no systematic changes in pre- and post-EMA measures or momentary EMA reports, suggesting women were not reactive to the EMA protocols. Completing 1–2 weeks of EMA does not appear to affect body dissatisfaction, mood, or attitudes in non-clinical or at-risk samples of women. These studies provide evidence that EMA methods can be used to assess real-world body image experiences without undue concern about measurement reactivity.